Investigating knowledge regarding antibiotics and antimicrobial resistance among pharmacy students in Sri Lankan universities - Sakeena, M. H.F.; Bennett, Alexandra A.; Jamshed, Shazia Qasim; Mohamed, Fahim; Herath, Dilanthi R.; Gawarammana, Indika Bandara; McLachlan, Andrew (BioMed Central Ltd., 2018)
Background: Antimicrobial resistance (AMR) is a major challenge for global health care. Pharmacists play a key role in the health care setting to help support the quality use of medicines. The education, training, and experiences of pharmacy students have the potential to impact on patterns of antibiotic use in community and hospital settings. The aim of this study was to investigate antibiotic use, knowledge of antibiotics and AMR among undergraduate pharmacy students at Sri Lankan universities and to compare this between junior and senior pharmacy student groups. Methods: A cross-sectional study was conducted at the six universities in Sri Lanka that offer pharmacy undergraduate programmes. All pharmacy students in each university were invited to participate in this study using a self-administered questionnaire with ethics approval. The study instrument comprised five major sections: demographic information, selfreported antibiotic use, knowledge of antibiotic uses in human health, knowledge of AMR and antibiotic use in agriculture. Descriptive data analyses were conducted and Chi-squared analysis was used to explore associations between different variables and level of pharmacy education. Results: Four hundred sixty-six pharmacy students completed the questionnaire. A majority of participants (76%) reported antibiotic use in the past year. More than half (57%) of the junior pharmacy students incorrectly indicated that antibiotic use is appropriate for the management of cold and flu conditions. Senior pharmacy students (n = 206) reported significantly better antibiotic knowledge than junior students (n=260), p < 0.05. Overall pharmacy students showed good understanding of AMR and their knowledge level increased as the year of pharmacy study increased. Conclusions: This study found that pharmacy students commonly report using antibiotics. Junior students report some misconceptions about antimicrobials. A comparison between junior and senior pharmacy students suggests that pharmacy education is associated with improved understanding of appropriate antibiotic use and AMR among undergraduate pharmacy students in Sri Lanka.